Pengaruh Kompensasi terhadap Kepuasan Kerja Karyawan pada PT Deltra Jaya Karya Makassar - Khatimah, Annisa Khusnul; Imasita; Serpian; Ekadina, Dian Nurisa; Rahmatillah (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
This research aims to determine 1) the provision of employee compensation at PT Deltra Jaya Karya Makassar; 2) employee job satisfaction at PT Deltra Jaya Karya Makassar; 3) the effect of compensation on employee job satisfaction at PT Deltra Jaya Karya Makassar. This study uses a quantitative approach with data collection methods using questionnaires and interviews. The sample in this study amounted to 35 respondents taken using the saturated sample method. Data analysis was carried out by simple regression analysis using SPSS Version 30 for windows. Testing of the questionnaire used validity and reliability tests. The inferential statistical analysis used in this study was simple linear regression, t-test, determination coefficient analysis (r2), and Spearman test. The results of this study indicate that 1) the provision of employee compensation at PT Deltra Jaya Karya Makassar is very good, 2) employee job satisfaction at PT Deltra Jaya Karya Makassar is very good, 3) compensation has an effect on employee job satisfaction at PT Deltra Jaya Karya Makassar.